Sustainable organisation management system: properties and factors - A. A. Dolgaya (Управление)
The ongoing degradation of natural resources and climate change are the focus of close attention of the global and business community. Sustainable development goals have been formulated at the highest levels of global economic governance. However, the existing trends are not broken and, obviously, a critical mass of business on a global scale is being conducted contrary to the declared direction. The purpose of the study is to identify the necessary characteristics of the management system of a sustainable organisation and the driving forces of its development. To achieve this goal, the author used the method of conceptual analysis. The systematisation of the research results was carried out on the basis of the author’s concept of the architectonics of the organisation’s management system. The approaches used to the formation of sustainability and management models of sustainable organisations were analysed both in the form of cases and in an analytical form. As a result of the study, the author revealed the features of managing a sustainable business organisation. Fundamental among them is the leader’s set of values. It is a necessary factor for the existence of the organisation. This particular set of values the author calles “sustainability”, and it determines the proper functioning of other system elements: organisational culture, performance indicators and internal organisational standards. The most significant sign of the “sustainability” set of values influence on the management system are investment decisions. In particular, the most striking indicator of the sustainability of the management system is the priority of long-term goals over short-term ones in the choice of production technologies in the company’s development process. The study confirmed the need for an integrated approach to assessing the sustainability of business organisations. The results of the study were used to create a conceptual architectonics of a sustainable organisation management system.